Strategic partnerships in the implementation of bonded recycling zones to support circular economy in Banten, Indonesia - Wahyudi, Imam Tri; Riesfandiari, Indri; Umardani, Agustyan; Nuryanto, Tony; Firman, Firman (Educoretax, 2024)
The purpose of this study is to explore the strategic partnerships role of Bonded Recycling Zones (KDUB) in facilitating Indonesia's transition to a circular economy and enhancing sustainable development. Utilizing a qualitative research approach, the study employs in-depth interviews with key stakeholders from various government agencies and the recycling industry, alongside a comprehensive analysis of policy documents. The findings reveal significant opportunities within the KDUB framework, yet also highlight critical gaps in inter-agency coordination, particularly in monitoring and evaluation processes, which are vital for aligning recycling practices with national strategic objectives and environmental standards. The research also underscores the positive impact of fiscal incentives on the recycling sector, while identifying the necessity for more efficient licensing procedures and clearer regulatory guidelines. This study offers original insights into the complexities of policy implementation in the context of circular economy initiatives, providing valuable recommendations for enhancing the effectiveness of KDUB policies and fostering stronger governmental collaboration.